Studies On A Power Signal Processor For Power Supply Quality Assessment - Kanaesalingam, Shri Rajini Kanth (2007)
This research is to investigate the application of a power signal processor in power system classification and assess power quality of supply. This study specifically applies adaptive neural network approach consisting of linear adaptive neurons called Adaline for tracking simultaneous change in system frequency and harmonic content in power system signals.